2004
DOI: 10.1111/j.0906-6705.2004.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of porphyria cutanea tarda in Chile: Identification and functional characterization of mutations in the uroporphyrinogen decarboxylase gene

Abstract: The porphyrias are heterogeneous disorders arising from predominantly inherited catalytic deficiencies of specific enzymes in heme biosynthesis. Porphyria cutanea tarda (PCT) results from a decreased activity of uroporphyrinogen decarboxylase, the fifth enzyme in heme biosynthesis. The disorder represents the only porphyria that is not exclusively inherited monogenetically. In PCT, at least two different types can be distinguished: acquired/sporadic (type I) PCT, in which the enzymatic deficiency is limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 35 publications
(65 reference statements)
2
19
0
1
Order By: Relevance
“…Genotype may contribute to iron overload with variable penetrance and phenotypic expression may be influenced by cofactors (8,(28)(29)(30) and other additive individual factors (1,5,28). It is therefore reasonable to observe a lack of significance in the correlation between iron blood indicators and body stores, such as skin and liver over a long time-period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotype may contribute to iron overload with variable penetrance and phenotypic expression may be influenced by cofactors (8,(28)(29)(30) and other additive individual factors (1,5,28). It is therefore reasonable to observe a lack of significance in the correlation between iron blood indicators and body stores, such as skin and liver over a long time-period.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore reasonable to observe a lack of significance in the correlation between iron blood indicators and body stores, such as skin and liver over a long time-period. This raises the possibility that, in some cases, there is a differential cellular iron handling, which results in variable accumulation of iron (5,6,8,15,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…The largest of these studies (1 ) identified 19 fPCT cases in 84 patients, but because DNA analysis was performed only in patients with low UROD activity, the frequency of fPCT might have been underestimated by a few percent. The 2 other studies reported the familial form to constitute about 25% of cases when UROD gene analysis was performed in all patients [53 and 61 patients, respectively (3,5 )], whereas 9 of 18 PCT patients in a Chilean study had familial disease (6 ). Most (74%) of the fPCT cases in our study were caused by 2 frequently occurring mutations, c.578GϾC and c.636ϩ1GϾC.…”
Section: Discussionmentioning
confidence: 41%
“…The disease is caused by a deficiency in uroporphyrinogen decarboxylase (UROD), the fifth enzyme in the heme synthesis pathway, and can be classified into several types, familial PCT (fPCT) and sporadic PCT (sPCT) being the most common. fPCT, an autosomal dominant disorder of low penetrance characterized by low UROD activity in all cells, constitutes about 25% of the cases in most populations (1)(2)(3)(4)(5)(6)(7). The level of UROD activity in erythrocytes has traditionally been used to distinguish between fPCT and sPCT, because sPCT shows reduced UROD activity only in the liver.…”
Section: © 2009 American Association For Clinical Chemistrymentioning
confidence: 99%
“…1). Bis heute wurden mehr als 100 Mutationen des Gens dieses Enzyms bei Patienten mit familiärer PCT nach gewiesen [3,16]. In der Regel reicht aber eine Mutation nur auf einem Allel nicht aus, um zur klinischen Manifestation einer PCT zu führen.…”
Section: Genetik Und Pathogeneseunclassified